My magnolia summer : a novel - Frank, Victoria Benton (William Morrow, an imprint of HarperCollinsPublishers, 2023)
Returning home when Gran, the treasured matriarch, falls in a coma after a car accident caused by her mother, Maggie finds Sullivan's Island is holding even more secrets as she feels herself changing like the Atlantic tides, rediscovering the roots she left behind and finding love.